Autonomy and democratic governance in Northeast India - Singh, M. Amarjeet (London : Routledge India, 2022)
This volume studies the various forms of ethnic autonomy envisioned within and outside the purview of the Sixth Schedule of the Indian Constitution. It explores the role of the British Indian administration and the Constituent Assembly of India in the introduction and inclusion of the schedule and the special provisions granted under it. Drawing on case studies from the states of Assam, Manipur, Meghalaya, and Sikkim in Northeast India and Darjeeling in North Bengal, it examines whether the practice of granting autonomy has been able to fulfil the political aspirations of the ethnic communities and how far autonomy settles or eases conflict. It also discusses sub-state nationalism and if it can be accommodated within autonomy, and studies the views of the central government and state governments towards such autonomy. An important contribution towards understanding Indiaś federal structure, the volume will be indispensable to students and researchers of politics, democracy, Indian Constitution, law, self-governance, political theory, and South Asian studies.
Section I: Understanding Autonomy 1. The Sixth Schedule to the Constitution of India: Emergence and DevelopmentJangkhongam Doungel2. Revisiting Sixth Schedule and Demand for Separate States in Northeast India: A Paradox of Political AutonomyMayengbam Nandakishwor Singh3. State within a State: Analysing the Issues and Challenges of Autonomous CouncilsAshutosh Tripathi and Gautam Kumar Section II: Autonomy and Electoral Politics 4. Contextualising Democratic Governance in Bodoland: Changes and ChallengesAnkur Jyoti Bhuyan, Tarun Gogoi and Partha Pratim Borah5. Challenging Predicaments of Electoral Politics of an Autonomous District Council:The case of Bodoland Territorial Areas District (BTAD), AssamNironjoy Islary6. The Working of the Autonomous District Councils in Manipur in Theory and PracticeThangkhanlal NgaihteSection III: Traditional Institutions, Autonomy Movement and Cooperatives7. Traditional Institutions, State Recognition and Democracy in Sikkim: Reconciling Tradition with ModernityDurga Prasad Chhetri8. Subject and Citizen: The Autonomy Question and Dzumsa in SikkimSunil Pradhan 9. The Crisis within: Can the Autonomous District Councils survive in Meghalaya?Dhiraj Kumar Borkotoky10. Autonomy Movements of Bodos and Chutias of Assam: A Comparative StudyPallabi Deka and Tribedi Chutia11. The Trajectory from Darjeeling Gorkha Hill Council to Gorkhaland Territorial Administration: A Fragile Administrative Autonomy in DarjeelingKabindra Sharma, Sanghamitra Choudhury and Debojyoti Das12. Understanding Autonomy Movement of the Misings in AssamBhaskar Pegu13. Autonomy and Democratisation through Cooperatives: Change from WithinAloke N. Prabhu
Keywords: India, Northeastern -- History -- Autonomy and independence movements; Democracy -- India, Northeastern; Constitutional law -- India; India, Northeastern -- Politics and government; POLITICAL SCIENCE / Political Ideologies / Democracy; POLITICAL SCIENCE / Government / State & Provincial; POLITICAL SCIENCE / Constitutions